Implementation of the Polluter Pays Principle in Environmental Law Enforcement in Indonesia - Farrel Salma Fadhilah; Immamulhadi; Dadang Epi Sukarsa (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
This study examines the effectiveness of the Polluter Pays principle in Indonesia’s environmental law enforcement framework following the enactment of the Job Creation Law. It specifically analyzes how regulatory changes have affected the accountability of business actors for environmental pollution and damage. Using a normative juridical approach, this research reviews statutory regulations, court decisions, and legal doctrines to assess the coherence between legal norms and their implementation. The study finds that although the Polluter Pays principle is formally embedded in the Environmental Protection and Management Law, the Job Creation Law, and Government Regulation No. 22/2021, its practical enforcement remains ineffective. This research identifies a critical gap between normative regulation and enforcement, primarily driven by the shift toward risk-based licensing, which weakens environmental permitting, reduces public participation, and limits oversight capacity. As a result, environmental governance becomes increasingly administrative, enabling business actors to avoid substantive liability. This study contributes to the development of environmental law by demonstrating that regulatory simplification under the Job Creation Law has structurally undermined the operationalization of the Polluter Pays principle. It highlights the need to strengthen enforcement mechanisms, enhance institutional oversight, and ensure greater legal protection for affected communities, including Indigenous peoples, to achieve ecological justice.